Gestión de control bajo teletrabajo en las operaciones bancarias y seguridad de la información en el departamento de reclamos de una entidad financiera - Valverde Arcos, Dáyaner Andrés (2022)
The present study entitled "Control management under teleworking in banking operations and information security in the claims department of a financial institution"; has been developed from the problems generated by the pandemic, where several organizations operated in complex and unstable business environments. The claims department of a financial entity, in order to preserve the occupational safety of the personnel, had to motivate the customer service by means of the teleworking system. The investigative development had a mixed approach of descriptive character with the application of the analytical method; using as techniques the documentary analysis, the survey, the interview and the direct observation; and as instruments the sources of first level, the questionnaire and the observation card in a sample conformed by 33 persons. The diagnosis of the control management under the modality of teleworking identified the increase of the workload of each of the workers; being the most susceptible operations the claims for judicial retentions, which gave way to the presentation of claims or complaints by the customers for the misuse of the information provided; for this a proposal of improvement of the control of the customer service in the processes of claims under the modality of teleworking that includes the change of the organizational structure; code of ethics and manual of functions is raised; obtaining an average of acceptance of the phases of 3. 56 points, which indicates that the experts are in agreement with the proposed and that the content has a medium level of risk (3.66 average), so it can be concluded that there is a vast theoretical support that allows to base the management of telework control in banking operations and information security; however, the gaps of information leakage must be solved.